2019
DOI: 10.1007/s00784-019-02826-y
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of postoperative bone healing of cystic lesions of the jaw—a retrospective study

Abstract: Objectives There is a long history of studies into cystic lesions of the jaws. However, there is little data on postoperative bone regeneration. The aim of the study was to calculate the size of the residual bone lesions after cystostomies and cystectomies to predict the postoperative bone healing. Material and methods This retrospective study focused on patients undergoing cystectomy (n = 114) or cystostomy (n = 86), who were treated for cystic lesions between 2010 and 2015. New formulas were developed to mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…Both imaging protocols have observed the underestimation of actual cystic lesion size, whereby recent reports indicate that automated volume determination of osseous lesions is faster but not superior to the manual acquisition, supporting this study's evaluation method [41]. Nevertheless, accurate volumetric assessment of the mandibular lesions is crucial, as the size of the cyst and its proximity to vulnerable structures, such as the inferior alveolar nerve or adjacent teeth, are essential in choosing the most suitable surgical treatment option for the patient [42,43].…”
Section: Discussionsupporting
confidence: 50%
“…Both imaging protocols have observed the underestimation of actual cystic lesion size, whereby recent reports indicate that automated volume determination of osseous lesions is faster but not superior to the manual acquisition, supporting this study's evaluation method [41]. Nevertheless, accurate volumetric assessment of the mandibular lesions is crucial, as the size of the cyst and its proximity to vulnerable structures, such as the inferior alveolar nerve or adjacent teeth, are essential in choosing the most suitable surgical treatment option for the patient [42,43].…”
Section: Discussionsupporting
confidence: 50%
“…However, the use of such a mathematical formula can be cumbersome in multi-locular lesions. Also, Sacher et al [ 20 ] who used OsiriX software, concluded that using the formula is easy to use and allows for an accurate and precise prediction of the amount of time needed for bone regeneration after both cystostomy and cystectomy. This means that the formula can be used for comparable conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Despite extensive research into changes in cyst areas and volumes [ 10 , 11 ], few prediction models exist today. A recently proposed linear regression approach for cyst diameters [ 12 ] can be easily implemented in a clinical setting but shows several shortcomings from physiological and statistical perspectives. Most importantly, cyst shrinkage is not linear [ 13 ].…”
Section: Introductionmentioning
confidence: 99%